Pengaruh Penggunaan Paylater Terhadap Perilaku Impulse Buying Pengguna E-Commerce di Indonesia - Rahmatika Sari (Jurnal Riset Bisnis dan Investasi, 2021)
The development of e-commerce has had an impact on payment methods which were originally only known as cash payments, paper-based, card based, are now being introduced with new electronic-based payment systems such as m-banking, virtual accounts, payment applications. Paylater is a type of online credit payment. Paylater allows its users to have a credit card without a card and without a complicated manufacturing process. This study uses a quantitative descriptive analysis method so that the data used is the result of distributing questionnaires to 404 samples who meet the criteria. The results of this study indicate that the ease of use oftechnology paylaterhas an effect of 6.4% on the impulsive buying behavior ofusers e-commerce in Indonesia. From the results of data processing, it can be concluded that the ease of use oftechnology paylater byusers e-commerce in Indonesia is very good andusers paylater tend to make impulse buying when shopping